The Scientific Use of Archives: Case Studies from London Metropolitan Archives Highlighting the Importance of STEM (Atlanti, 2016)
This paper illustrates the scientific uses for which archives can be a major contributing factor in the fields of education and research. For too long archives have only been the preserve of the historian but there are many more uses and factors of relevance to today’s modern world. This paper reveals some of the ways that archives have been unlocked and used more widely by different groups of researchers. Whilst historians and genealogists have concentrated their studies on names and places, there are many more uses for archives to explain some of the complexities and specialisms of human activity. London Metropolitan Archives (LMA) has sought to extend the use of its City archive collections in new ways which could be made relevant to broad subject areas known as STEM (Science, Technology, Engineering and Mathematics). The archives believed that historical sources could add depth to the teaching of subjects like science.
Keywords: science; technology; engineering; mathematics; London Metropolitan Archives